Concealed pied‐piping in Russian: On left‐branch extraction, parasitic gaps, and the nature of discontinuous nominal phrases. (19th January 2023) - Bondarenko, Tatiana; Davis, Colin
Abstract: We use parasitic gaps to examine left‐branch extraction from nominal phrases in Russian. We observe that the interpretation of a parasitic gap in a context with left‐branch extraction is the same as the interpretation assigned when an entire nominal phrase is moved. Thus we argue that Russian left‐branch extraction involves concealed pied‐piping of an entire nominal phrase, rather than true extraction of a left branch. We go on to explore the consequences of this analysis for several other topics.